Assessment of Genetic Diversity of Some Finger Millet (Eleusine coracana (L.) Gaertn. Accessions Using Morphological Markers - D.V.S. Kaluthanthri (Journal of Tropical Forestry and Environment, 2017)
Abstract Germplasm characterization is an important link between conservation and utilization of plant genetic resources. The study was conducted to characterize randomly selected 20 finger millet germplasm accessions obtained from Plant Genetic Resource Center, Gannoruwa, Sri Lanka using morphological markers. Morphological study was carried out using Randomized Complete Block Design (RCBD) and 15 morphological markers were recorded. Analysis of variance (ANOVA) results for quantitative morphological characters revealed that all quantitative morphological characters measured differed significantly (p˂0.05) among the accessions used for the study, indicating higher levels of morphological diversity. According to the ANOVA results, days to flowering and days to maturity show high level of predictive capability while flag leaf length and number of productive tillers show comparatively low level of predictive capability. Principal component analysis indicated that morphological characters such as days to flowering, finger number and yield per plant were the important traits contributing for the overall variability implying that breeding effort on those traits can meet the targeted objective. The clustering pattern of studied finger millet accessions based on morphological markers comprised of two major clusters. Both clusters comprised of Indian accessions those conserved at PGRC, Gannoruwa and as well as Sri Lankan accessions. Results of the study suggest a considerable morphological variability, which could exist among the studied traits. Furthermore, this study revealed that the genetic diversity existed irrespective to the geographical origin. This finding justifies the importance of germplasm characterization.